PEMODELAN PERUBAHAN LAHAN DAN TUTUPAN LAHAN BERBASIS MARKOV-CHAIN DI KABUPATEN GUNUNG KIDUL - Rahmawati, Septi Sri; Setyowati, Ratih; Ramlah; Azizah, Salsabila Nur; Ardiansyah, Ramadhani Muhammad Yusuf; Saikhu, Ahmad (Departemen Tanah, Fakultas Pertanian, Universitas Brawijaya, 2025)
The standard values of quality and quantity of living needs continue to increase over time, leading to competition in the utilization of agricultural and non-agricultural land. This results in uncontrolled land use conversion. Land use changes in Gunungkidul between the 1940s and 1970s caused widespread deforestation, making the area barren. Conservation efforts up to the early 2000s yielded positive results. However, population growth and the expansion of activity centers in Gunungkidul during the 2000s may trigger further deforestation. This study analyzes spatiotemporal land use changes in Gunungkidul Regency over the period 2015–2023. Land use data were obtained from Landsat and Sentinel-2 satellite imagery and analyzed using Geographic Information Systems (GIS) and accuracy assessment through ground checks. The results show significant land use changes, particularly the conversion of vegetation into built-up areas, with an increase/decrease in area from 2015 to 2023 of 72.65%. The most significant changes occurred in Wates District, the administrative center of Gunungkidul Regency, forming a pattern concentrated around service centers and spreading linearly along access routes to these centers. Land changes were also observed in the northern and southern regions with a scattered pattern. These changes are driven by population growth and regional development in Gunungkidul Regency. Land use changes may lead to land degradation, highlighting the importance of this study in providing crucial information for better spatial planning and land management in the future.